Successful Treatment of Anemia With Ringed Sideroblasts Induced by Antidepressants Through Vitamin B6 Supplementation and Discontinuation of Antidepressants - Sanshiro Nakao; Chiaki Nakaseko; Chikako Ohwada; Keisuke Kirito; Asuka Shibamiya; Akane Tanaka; Reiko Watanabe; Naomi Shimizu (Case Reports in Hematology)
Vitamin B6 (VB6) is a vital coenzyme for δ-aminolevulinic acid synthase (ALAS) in heme biosynthesis. We report a 49-year-old male with severe microcytic anemia and ringed sideroblasts initially diagnosed as myelodysplastic syndrome (MDS). VB6 deficiency, attributed to long-term amoxapine use, was identified. His anemia improved significantly with VB6 supplementation and resolved completely after discontinuing amoxapine. This case highlights the need to consider VB6 deficiency in anemia with ringed sideroblasts.